Textbook of Pathology - Mohan, Harsh (New Delhi : Jaypee, 2015)
Fully revised seventh edition presenting latest advances in pathology. Includes free booklet 'Pathology Quick Review and MCQs' (9789351523703). Previous edition published in 2010
Keywords: Pathology -- Textbook; Pathology; HEALTH & FITNESS -- General. -- Diseases; Pathological Processes